201k views
3 votes
2logx+3logy=0 find y in term of x

User Mindau
by
5.7k points

2 Answers

4 votes

Explanation:


{:}\longrightarrow
\sf 2log_x+3log_y=0


{:}\longrightarrow
\sf 3log_y=-2log_x


{:}\longrightarrow
\sf {\cancel {log}}_y={\frac {2}{3}}{\cancel{log}}_x


{:}\longrightarrow
\sf y={(2)/(3)}x

User Tenwest
by
6.3k points
6 votes

Answer:

  • y = x^(-2/3)

Explanation:

Given

  • 2log x + 3log y = 0

Finding y in terms of x

  • 3log y = -2log x
  • log y = -2/3log x
  • log y = log x^(-2/3)
  • y = x^(-2/3)
User Facebook
by
6.1k points